Dr. Carmelita Quebengco received the plaque of recognition - Quebengco, Carmelita I. (Animo Repository, 1999)
DLSU-Manila EVP Dr. Carmelita Quebengco received the plaque of recognition from Aniceto Sobrepena, Metrobank Foundation Executive Officer. The award was given in acknowledgement of Literature faculty Dr. Marjorie Evasco-Pernia who was one of the 1999 Metrobank Outstanding Teachers.